FACTORS RELATED TO WORK STRESS IN THE ONLINE MOTORCYCLE TAXIS DRIVER COMMUNITY IN DEPOK CITY IN 2022 - Shalsa Biella; Noor Latifah; Fini Fajrini (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
The incidence of stress is considered quite high, where more than 350 million people in the world experience stress. And according to the World Health Organization stress is a disease with the 4th rank in the world. It is recorded that around 10% of the population in Indonesia experience stress. Based on the results of previous research, it was found that in the coverage area of ​​Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek), there were 19 people (63.3%) online motorcycle taxi drivers who experienced stress, then online motorcycle taxi drivers who did not experience stress as many as 11 people. (36.7%). The purpose of this study was to find out the factors related to work stress in the online motorcycle taxi driver community in Depok City in 2022. The method in this study used a quantitative approach with a cross-sectional study design with a sample size of 130 respondents. The results of the bivariate analysis test showed that the variables related to work stress are age (p-value 0,000), gender (p-value 0,003), marital status (p-value 0,000), and workload (p-value 0,000). The variable that is not related to work stress is interpersonal relationships (p-value 0,236). This study concludes that the factors that have a relationship with work stress are age, gender, marital status, and workload. While the variables of interpersonal relationships have no relationship.